2014
DOI: 10.5352/jls.2014.24.11.1224
|View full text |Cite
|
Sign up to set email alerts
|

Antiadipogenic Effects of Red Radish (Raphanus sativus L.) Sprout Extract in 3T3-L1 Preadipocytes

Abstract: The red radish (Raphanus sativus L.; RR) sprout is a plant of the cruciferous family. In this study, we elucidated the effect of the water extract of RR sprout (RRSE) against α-amylase, α-glucosidase, and pancreatic lipase enzyme activity and adipogenesis in 3T3-L1 preadipocytes. α-amylase, αglucosidase, and pancreatic lipase enzyme activity was inhibited in a concentration-dependent manner by RRSE treatment. RSSE also abolished adipocyte differentiation and lipid and triglyceride accumulation without cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Additionally, we showed that optimally produced 2 days PRSP extract effectively inhibited MDI‐induced adipogenesis and lipogenesis. The anti‐obesity effects of RRSP have been previously reported 23‐25 . However, unlike our conditions, these studies have used RRSP extracted in water at 90 °C, 24 from which SFEN could not be thoroughly extracted or stably present, 25 by targeting other bioactive compounds such as anthocyanin in RSP rather than SFEN.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, we showed that optimally produced 2 days PRSP extract effectively inhibited MDI‐induced adipogenesis and lipogenesis. The anti‐obesity effects of RRSP have been previously reported 23‐25 . However, unlike our conditions, these studies have used RRSP extracted in water at 90 °C, 24 from which SFEN could not be thoroughly extracted or stably present, 25 by targeting other bioactive compounds such as anthocyanin in RSP rather than SFEN.…”
Section: Resultsmentioning
confidence: 99%
“…The anti‐obesity effects of RRSP have been previously reported 23‐25 . However, unlike our conditions, these studies have used RRSP extracted in water at 90 °C, 24 from which SFEN could not be thoroughly extracted or stably present, 25 by targeting other bioactive compounds such as anthocyanin in RSP rather than SFEN. Thus, this is the first time that the optimal extraction conditions have been adjusted to target ITCs including SFEN in PRSP and evaluate any anti‐obesity effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…treatment showed a significant (P<0.01) decrease in the body weight up to 5 g than the high-fat diet control group. Moreover, Kim et al (2014) stated that using RRSE of over 200 μgml -1 could inhibit the expression of adipogenic transcription factors (PPARγ, C/EBPα, and SREBP-1) and proteins (adiponectine, perilipin, FAS, and FABP4) in 3T3-L1 preadipocytes. Data from this work suggested that a consumed diet with RRS showed an anti-obesity effect and this may be attributed tothe high content of fibers and its content of phenolic compounds.…”
Section: The Sixth Daymentioning
confidence: 99%
“…Red radish “ Raphanus sativus ” family “ Brassicaceae ” is a radical crop that is eaten raw, pickled, or cooked (Otsuki et al 2004 ; Tamura et al 2010 ). Red radish is rich in important vitamins and minerals (folic acid), anthocyanins, potassium (K), calcium (Ca), copper (Cu), iron (Fe), phosphorus (P), zinc (Zn), anthocyanins, fiber, and antioxidants making it a potential candidate in avoiding cardiovascular diseases, dyslipidemic conditions, and hypoglycemic influences (Kim et al 2014 ; Anna et al 2016 ; Khedr and El Sheikh 2016 ). Vivarelli et al ( 2016 ) suggested that radish juice could be a good nutraceutical product with efficient antioxidant, hypolipidemic, and anti-obesity effects.…”
Section: Introductionmentioning
confidence: 99%